2015
DOI: 10.1080/10255842.2015.1082552
|View full text |Cite
|
Sign up to set email alerts
|

Spiral blood flow in aortarenal bifurcation models

Abstract: The presence of a spiral arterial blood flow pattern in humans has been widely accepted. It is believed that this spiral component of the blood flow alters arterial haemodynamics in both positive and negative ways. The purpose of this study was to determine the effect of spiral flow on haemodynamic changes in aorta-renal bifurcations. In this regard, a computational fluid dynamics analysis of pulsatile blood flow was performed in two idealised models of aorta-renal bifurcations with and without flow diverter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Similar to our study, they found an increase in flow rate at lower angles. Javadzadegan et al [36,37] evaluated the effects of blood flow spirality on the recirculation zone length. To obtain precise results, they needed a spiral velocity component with a parabolic flow boundary condition at the aorta inlet.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, they found an increase in flow rate at lower angles. Javadzadegan et al [36,37] evaluated the effects of blood flow spirality on the recirculation zone length. To obtain precise results, they needed a spiral velocity component with a parabolic flow boundary condition at the aorta inlet.…”
Section: Discussionmentioning
confidence: 99%
“…As an advancement of 2D phase contrast MRI techniques (1), four-dimensional phase contrast (4D Flow) flow mapping has emerged as a rich source for assessment of hemodynamics (2)(3)(4). Post-processing of 4D Flow MRI allows measuring several quantitative features that characterize the secondary flow patterns in the aorta and pulmonary artery (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Turbulence, helical flow patterns, eccentricity and other secondary flow patterns are associated with many cardiovascular diseases (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%